Perjanjian Perdagangan Bebas (FTA) antara Malaysia dan Negara Kerjasama Teluk (GCC): satu Kajian Empirik - Tamat Sarmidi; Sanep Ahmad; Kamaruzaman Yusoff; Hazwani Mustafa Kamil Aznie (Institut Kajian Rantau Asia Barat, 2010)
The main objective of this research paper is to examine the possible trade impact on the proposed Free Trade Agreement (FTA) between Malaysia and Gulf Cooperation Council (GCC). The study employ panel gravity model on export, import, income, population, size of the country, distance between countries, bilateral exchange rate, and two dummy variables to represent GCC countries and countries that have FTA with Malaysia from 2002 to 2009. In general, the finding shows the significant impact of the economic size and distance to the total bilateral trade with Malaysia. However, the study statistically fail to prove the significant effect of FTAs to the total trade.